Use and quality of point-of-care microscopy, urine culture and susceptibility testing for urinalysis in general practice - Ida Kollerup; Anne Kathrine Aagaard Thomsen; Jette Brommann Kornum; Kirsten Inger Paulsen; Lars Bjerrum; Malene Plejdrup Hansen (Taylor & Francis Group, 2022)
Objective: To describe the use and quality of point-of-care (POC) microscopy, urine culture and susceptibility testing performed in general practice in Northern Denmark from 2013 to 2018. Design: Descriptive study Setting: General practices receiving a fee for examining urine samples. Subjects: Simulated urine samples containing uropathogenic bacteria distributed by the organisation for improvement of microbiological quality (MIKAP). Main outcome measures: Percentage of use and correct answers for microscopy, culture and susceptibility testing. Results: A total of 5361 samples were analysed by the use of microscopy (39.7%), culture (66.0%) and/or susceptibility testing (76.5%). For culture, Flexicult SSI urinary kittm (87.6%) demonstrated the highest percentage of correct answers followed by chromogenic agar (85.1%) and 2-plate dipslide (85.2%). Mueller Hinton agar with tablets had the highest percentage of correct answers for susceptibility testing of most bacterial strains (84.6%), followed by Flexicult (77.2%). Furthermore, susceptibility testing with tablets (range: 76.1-84.6%) was found to be more accurate than discs (range: 72.9-75.5%). Overall, the highest percentage of correct answers was obtained when examining urine samples containing Escherichia coli: Microscopy (78.3%), culture (87.0%) and susceptibility testing (range: 84.3-90.7%). Conclusion: The quality of POC testing in general practice was high when examining urine samples containing the most common uropathogen E. coli. Surprisingly, susceptibility testing was more frequently used than culture. This approach may compromise the treatment decision as only cultures contribute with information about the flora composition and bacterial quantification. Interestingly, microscopy was the least used method even though the result may be reached within a few minutes.Key points The quality of POC tests (microscopy, urine culture, susceptibility testing) performed in general practice was high when examining urine containing E. coli, whereas difficulties were observed for samples including S. saprophyticus or K. pneumoniae. Susceptibility testing was more often performed than urine culture, which indicates a problem as only urine cultures contribute with information about the flora composition and bacterial quantification.